Audio–Visual Conditions and Restorative Responses in Urban Village Public Spaces: Evidence from a VR-Based Repeated-Measures Experiment in Shenzhen, China - Da Yang; Jinying Tao; Qi Meng; Yaonan Ai (Buildings, 2026)
As urban renewal shifts from expansion-led development toward quality improvement of existing urban areas, the restorative quality of urban village public spaces has become an important concern in high-density human settlements. Existing restorative environment research has focused mainly on parks, green spaces, waterfronts, and other settings with strong natural attributes, while audio–visual studies have often examined environmental perception, restorative appraisal, or physiological response as separate analytical components. Limited evidence therefore exists on how scene-level visual and acoustic characteristics, subjective sensory appraisal, perceived restoration, and short-term physiological responses are related within the same analytical framework in high-density urban village public spaces. This study investigated six selected public spaces in Shenzhen urban villages using a VR-based repeated-measures experiment involving 33 participants and 198 participant–scene observations, together with computer vision indicators, psychoacoustic analysis, subjective evaluation, EDA and HRV monitoring, linear mixed-effects models, and multilevel models of statistical indirect associations. Green view index (B = 0.322, p < 0.001) and color complexity (B = 0.422, p < 0.001) were positively associated with perceived restoration, whereas building enclosure (B = −0.271, p < 0.001) and sound roughness (B = −0.328, p < 0.001) were negatively associated with perceived restoration. Green view index showed a positive indirect association with perceived restoration through visual perception (ab = 0.386, 95% CI [0.304, 0.484]), whereas roughness showed a negative indirect association through soundscape perception (ab = −0.277, 95% CI [−0.385, −0.176]). In the full six-scene models, negative objective interaction estimates were compatible with acoustic constraints on favorable visual associations, but several interaction coefficients were sensitive to scene omission and should be regarded as exploratory; at the subjective level, soundscape perception and visual perception showed a positive interaction (B = 0.095, p = 0.028). Leave-one-scene-out analysis showed that several scene-level main-effect and objective interaction estimates were sensitive to the omission of S5 or S2, whereas the directions of the green-view-index and roughness indirect associations were retained. Perceived restoration was positively correlated with the reversed EDA recovery score (r = 0.416, p < 0.001), whereas HRV showed a negative association with LAeq (B = −0.150, p = 0.008), suggesting different short-term response patterns across subjective and physiological measures. The findings suggest that restorative responses in the examined urban village scenes were associated with both subjective sensory appraisal and audio–visual interactions. The study contributes by integrating scene-level visual and acoustic characteristics, subjective sensory appraisal, perceived restoration, and short-term physiological responses within a high-density urban village context. For renewal practice, the results support the coordinated consideration of adverse sound sources, visible greenness, and visual order; however, the observed relationships should be interpreted as context-specific associations rather than as universal causal mechanisms or validated design thresholds.